Zonal cortical scarring and tubular thyroidization in kidney biopsies of patients with SLE—histologic indicator for antiphospholipid antibodies. (December 2018) - Shah, R; Brodsky, S V; Hebert, L; Rovin, B H; Nadasdy, T; Satoskar, A A
Antiphospholipid antibody syndrome (APS) is an acquired prothrombotic autoimmune disease caused by the presence of antibodies against anionic phospholipids or plasma proteins bound to phospholipids on cell membranes. It can be a primary disease or secondary to other autoimmune diseases, most commonly systemic lupus erythematosus (SLE). Laboratory testing for antiphospholipid antibodies (aPL) may be only transiently positive, so APS could be missed until a catastrophic thrombotic episode or pregnancy morbidity occurs. In the kidneys, this manifests as thrombotic microangiopathy (TMA), and patients present with hypertensive urgency and acute kidney injury. However, APS may not always have a catastrophic presentation but instead a more smoldering course. Kidney biopsy may not show obvious active TMA lesions but rather only chronic injury in the form of zonal cortical scarring and tubular thyroidization. Still, it may warrant anticoagulation therapy. So it is important to recognize this pattern of injury in the biopsy. Herein, we retrospectively study the correlation between presence of this histologic feature in kidney biopsies of SLE patients and positive aPL testing results (anticardiolipin antibodies and/or lupus anticoagulant). Kidney biopsies of SLE patients from 2004 to 2015 ( n  = 186) were screened for presence or absence of zonal cortical scarring. Their electronic medical records were reviewed for aPL results. Our study showed low sensitivity (33%) but higher positive predictive value (62%), specificity (89%) and negative predictive value (71%). This histologic finding is therefore not a sensitive screening tool, but if present, greatly increases the likelihood of underlying aPL. We want to emphasize that recognition of this histologic feature in the biopsies of SLE patients is important so as not to miss the opportunity to treat with anticoagulation therapy and possibly slow down the chronic renal damage.